The relative importance of anxiety and depression in pain impact in individuals with migraine headaches. - Tomé-Pires, Catarina; Solé, Ester; Racine, Mélanie; Galán, Santiago; Castarlenas, Elena; Jensen, Mark; Miró, Jordi (Elsevier, 2016)
Background: Psychological factors are thought to impact headache as triggering, maintaining, and exacerbating factors. A better understanding of the role that modifiable factors, such as anxiety or depression, play in the impact of migraine could help identify potential treatment targets in this population. Objectives: The objective of this study was to evaluate the relative importance of anxiety and depression as predictors of the impact of migraine on function. Thus, we aim to understand the relative importance that anxiety and depression have on the impact of migraines by assessing both and some life domains. Methods: Cross-sectional study involving forty-three individuals, mostly females (93%), with migraine headaches aged between 20 and 60 years old. Participants answered questions about headache pain intensity at the time of data collection and the usual in the past 30 days (0-10 Numerical Rating Scales) as well as other pain characteristics (i.e., duration, frequency, and duration), headache impact (vitality and social, role, and cognitive functioning), anxiety and depression by using the Hospital Anxiety and Depression Scale. Results: Anxiety (r=0.56, p<.001), but not depression (r=0.09, p=.59), was significantly associated with headache impact. Thus showing the relative importance that anxiety has on headache impact. Conclusions: The findings support a larger role for anxiety than depression in the impact of migraine headaches on patient function. There are a number of mechanisms by which anxiety could potentially influence the impact of headache on patient function, and this study highlights that anxiety could potentially be a trigger of headache activity. Implications: The findings thus suggest the possibility that treatments that focus on anxiety might be potentially more important for individuals with migraine than treatments that focus on depression, at least with respect to having a beneficial impact on the interference of headache with activity. Research is needed to evaluate the beneficial impact of anxiety treatment in individuals with migraine headaches. Clinicians should evaluate and consider treating, as appropriate and necessary, anxiety in patients with migraine.
Keywords: Dolor - Aspectos psicológicos; Depresión mental; Ansiedad; Cefalalgia; Migraña; Anxiety; Depression; Headache impact; Migraine